2005
DOI: 10.1093/intimm/dxh205
|View full text |Cite
|
Sign up to set email alerts
|

C3d binding to the circumsporozoite protein carboxy-terminus deviates immunity against malaria

Abstract: The immunogenicity of recombinant protein or anti-viral DNA vaccines can be significantly improved by the addition of tandem copies of the complement fragment C3d. We sought to determine if the efficacy of a circumsporozoite protein (CSP)-based DNA vaccine delivered to mouse skin by gene gun was improved by using this strategy. Instead, we found that C3d suppressed the protective immunity against Plasmodium berghei malaria infection and deviated immunity, most notably by suppressing the induction of antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Thus, these observations in mice might have implications for improving CSP vaccine design (18). Although the C-terminal region of P. berghei CSP has been associated with protection in mice (19,20), our C-terminal construct of PfCSP did not confer protection against a Tr P. berghei challenge. This result was reminiscent of a human trial in which a repeatless CSP construct did not protect the vaccinees (21).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, these observations in mice might have implications for improving CSP vaccine design (18). Although the C-terminal region of P. berghei CSP has been associated with protection in mice (19,20), our C-terminal construct of PfCSP did not confer protection against a Tr P. berghei challenge. This result was reminiscent of a human trial in which a repeatless CSP construct did not protect the vaccinees (21).…”
Section: Discussionmentioning
confidence: 80%
“…After submission of our manuscript for review, a report was published documenting a very similar pattern of attenuated antibody responses to plasmodial circumsporizoite protein (CSP) by fusion to three copies of C3d [23]. This report is of particular interest in that it provides evidence that physical interactions between C3d and the target antigen can decrease the immunogenicity of the C3d-antigen complexes.…”
Section: Discussionmentioning
confidence: 98%
“…Past studies on sporozoite vaccines have revealed a poor correlation between the protective efficacy of a vaccine and antibody titers. For examples, the complement fragment C3d-based PbCSP vaccine was capable of inducing strong antibody responses against CSP, but its protective efficacy, compared with the parent PbCSP vaccine, was reduced [33]. Studies in our laboratory are in progress towards development of an evaluation system which can detect the specific antibodies that contributed to the protective efficacy of a vaccine.…”
Section: Discussionmentioning
confidence: 99%